THE CONSUMPTION OF FRUITS AS A POTENTIAL ALTERNATIVE TO ACCELERATE THE RECOVERY PROCESS AFTER HIGH INTENSITY EXERCISE - Skinner, Sonja; Wade, Madison; Iacobacci, Courtney; Hutcherson, Roderick; Santos, Julia Matzenbacher dos (Revista Contexto & Saúde, 2020)
A prevalent desire in the sports world is the acceleration of post-exercise recovery; therefore, many studies have examined the use of dietary supplements before, during, and after exercise to determine the positive effects on athletes as a catalyst for recovery. Overall, studies have found that adaptations to regular exercise promotes advantageous reactions in the body to boost the immune system, prevent dyslipidemia and muscle loss, and increase bone density. However, exercise at an increased intensity or duration usually performed under competitive settings can deplete glycogen stores, increase lactic acid, form an excess amount of reactive oxygen species (ROS), increase tissue damage, and decrease immunologic function. This review incorporated studies that tested the use of fruits as a strategy to attenuate the period by which the body buffers the increase in acidity and inflammation, scavenge ROS and to regenerate muscle damage after high intensity exercise. Therefore, the effect of fruit intake rich in vitamins and those containing polyphenolic ring-based flavonoids and carbohydrates was discussed. Nutrient supplementation can enhance recovery after high intensity exercise, particularly fruits of red-blue color such as cherries and blueberries seem to decrease oxidative stress, inflammation, and muscle damage. In summary, each fruit has specific targets to offset body regeneration, avoid over training, and improve overall performance.